INNOVATIVE LEARNING MEDIA IN TEACHING 2D DRAWING MODIFICATION WITH CAD TECHNOLOGY - Selfia, Meliza; Hamdani, Aam; Komaro, Mumu (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2024)
The lack of understanding of students on 2D drawing modification material using CAD is the background for this research. The purpose of this study is to produce products in the form of video tutorial learning media, knowing the feasibility of experts, knowing user responses, and knowing the improvement of learning outcomes after using media. This study used quantitative research methods with a pre-experimental research design with the type of one group pre-test post-test design. Purposive sampling was conducted to select 34 samples from TPM grade XI learners. This research produces video tutorial learning media. The results of the feasibility assessment conducted by show that the video tutorial learning media that has been made is declared "very feasible". The results of media user responses obtained the category "very good". Learning outcomes after using video tutorial learning media have increased, this is reflected in the increase in student learning outcomes measured through the use of n-gain with an average score of 0.38 in the "medium" category. Thus, it can be concluded that this video tutorial learning media is very feasible for use on manufacturing engineering drawing elements.